1976
DOI: 10.1002/zamm.19760560802
|View full text |Cite
|
Sign up to set email alerts
|

Fließspannungen und Fließbedingung bei zyklischen Verformungen

Abstract: Bei zyklischer plastischer Verformung metallischer Werkstoffe treten bekanntlich im wesentlichen folgende Effekte auf: der Bauschingereffekt, ein Relaxationseffekt sowie der Effekt der zyklischen Entfestigung. In früheren Arbeiten [1, 2] wurden Ansätze zur analytischen Erfassung der genannten Effekte mitgeteilt. Diese Ansätze erfahren in dem folgenden Beitrag eine nochmalige Behandlung, wobei insbesondere ein neuer Ansatz für die zyklische Entfestigung eine wesentliche Verbesserung darstellt. Es werden allgeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…(iv) appears to have been first used by Backhaus [18] within the formalism of associative theory of plasticity.…”
Section: Appendix Amentioning
confidence: 97%
“…(iv) appears to have been first used by Backhaus [18] within the formalism of associative theory of plasticity.…”
Section: Appendix Amentioning
confidence: 97%
“…It was shown that the two surface model proposed by Krieg [11], in which the bounding surface is located outside the yield surface, is mathematically equivalent to the AF model if the bounding surface neither expands nor translates [21,30]. It was also shown that the hereditary integral model called the endochronic theory formulated by Valanis [9] as well as by Backhaus [10] can be reduced to the AF model if the kernel functions in the hereditary integral are taken to be exponential functions [31]. These two models therefore may overpredict both uniaxial and multiaxial ratchetting.…”
Section: Other Classical Modelsmentioning
confidence: 99%
“…They then extended it on the assumption that the dynamic recovery of ai is activated nonlinearly as ai approaches the critical state fi=0: (10) Fig. 3 (a) Incidentally, Jiang et al [35,36] showed that the material constants ƒÄi and ƒÁi in Eqs.…”
Section: Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the flow rule for kinematic hardening may utilize a hereditary integral to govern the evolution of the back stress (e.g. Backhaus, 1976). This framework was further extended to take into account such effects as the memory of maximal prestrain and the amplitude-dependent hardening in the case of cyclic loadings (cf.…”
Section: Introductionmentioning
confidence: 99%